2021
DOI: 10.1177/23743735211033752
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Patient Experiences During the COVID-19 Pandemic

Abstract: Emergency department (ED) utilization changed notably during the coronavirus disease 2019 (COVID-19) pandemic in the United States. The purpose of the study was to gain a more thorough understanding of ED patient experience during the early stages of the COVID-19 pandemic. This study used the consensual qualitative approach to analyze open-ended responses from post-ED patient experience surveys from February through July 2020. Comments were included in the analysis if they pertained to care during the pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…Patient satisfaction, which is directly associated with the quality of patient care, is a very important and challenging factor for emergency departments (13). Although would be expected for the increased workload and stress on healthcare workers due to the pandemic to have a negative effect on patient satisfaction (14), the present study found that the satisfaction level of the patients who were cared for in the emergency department due to COVID-19 was significantly higher than that of non-COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 77%
“…Patient satisfaction, which is directly associated with the quality of patient care, is a very important and challenging factor for emergency departments (13). Although would be expected for the increased workload and stress on healthcare workers due to the pandemic to have a negative effect on patient satisfaction (14), the present study found that the satisfaction level of the patients who were cared for in the emergency department due to COVID-19 was significantly higher than that of non-COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 77%
“…Regarding the identification of feelings experienced during hospitalization , 71.9% (n = 23) of the articles indicated that the patients and family members experienced difficult moments 47 during the hospitalization period, with feelings of loneliness 16 , 17 , 21 , 31 and isolation 16 , 17 , 21 , 29 , 31 , 40 , 41 due to the restrictions regarding visits and companions and a lack of contact between professionals and patients. 20 Feelings such as sadness, 23 , 26 , 46 fear, 17 , 18 , 20 , 22 , 24 29 , 32 , 33 , 46 anxiety, 17 , 22 , 28 , 38 , 41 , 46 worry, 17 , 20 24 , 32 , 33 , 46 nervousness, 22 guilt, 26 , 46 anger, 23 , 26 tiredness, 24 hopelessness, 46 frustration, 43 discrimination, 18 , 22 vulnerability, 29 , 32 , 46 and uncertainty 22 were also reported, associated with lack of knowledge about the disease and with the situation in which they found themselves. It is noted that the articles described concerns about the personal 21 or family 20 socioeconomic situation as aggravating factors, because of uncertainty of the economic and housing situation.…”
Section: Resultsmentioning
confidence: 99%
“…27 , 34 In addition, in relation to the interaction between professionals and patients, the nurses reported depersonalization of care, focusing on the care of the clinical conditions inherent to COVID-19, 39 including assistance in emergency sectors. 43 Still, a study that sought the satisfaction of hospitalized patients showed the interpersonal skills of doctors and nurses as lower patient satisfaction ratings. 19 However, in a study, it was stated that the care experience was identical when compared with the service before the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown a signi cant reduction in ED visits over the rst weeks of the pandemic [11,19]. The reasons might be that either patients avoided hospital visits due to fear of contracting COVID-19 or transmission of certain communicable diseases had slowed because of fewer human contact [14,17,20]. However, these studies did not assess changes in clinical characteristics, emergency status, and admission rate among ED attendees.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, severe acute respiratory syndrome (SARS) outbreak affected the medical service system and decreased the ED visits by 40% [13]. Similar to that of SARS outbreak, people became reluctant to hospitals due to panic and fear of contracting COVID-19 [14,15]. Relative to the pre-pandemic period, the delay in treatment from symptom onset to hospital arrival is common during a pandemic, resulting in worse prognoses and more urgent clinical conditions of patients; thus, ultimately increasing morbidity and mortality associated with both chronic and acute health conditions.…”
Section: Introductionmentioning
confidence: 99%